ANALYSIS OF PROBLEMS OF THE TROLLEYBUSES STEERING SYSTEM AND PERSPECTIVES FOR THEIR SOLUTION (Transport systems and technologies, 2018)
Electric transport is a necessary part of infrastructure of large cities and is used for the transportation of passengers or cargo. Therefore, the issue of its constant updating or modernization and improvement of some elements is acute. The analysis of problems during the operation of trolleybuses was carried out and the object of modernization of steering control on the basis of the trolleybus brand LAZ-E183 was determined.The purpose of the work is to develop steering control of simplified design and increased energy efficiency.The object of research is design the amplifiers of the steering system of trolleybuses. The subject of the study is processes and characteristics that affect energy efficiency of steering systems.The scientific novelty is an innovative solution to increase the energy efficiency of the steering system of trolleybuses through the use of an electric motor with rolling rotor, which allows to realize a high torque unlike traditional electric motors.The practical value of a new technical solution is develop an electric power steering system of trolleybus through the use of an electric motor with rolling rotor, as well as in reducing the size and simplified design of the steering booster.The application of the engine with rolling rotor makes it possible to reduce the power consumption of the on-board network by switching on the electric power steering only at the moment of turning the trolley, which also increases the energy efficiency of the steering control.
Keywords: steering, steering booster, energy efficiency power steering, electric power steering